The Impact of Inflation on the Business Cycle and Economic Growth: An Empirical Analysis - Sule, Sani Abdullahi; Hakim, Lukman; Putro, Tetuko Rawidyo; Pamungkas, Putra (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This paper investigates the complex relationship between inflation, business cycles, and economic growth, focusing on both theoretical and empirical perspectives. The primary aim is to under-stand how inflation impacts key economic variables such as investment, consumption, employ-ment, and productivity and to identify effective policy responses. Specifically, the study’s objec-tives are to examine the mechanisms through which inflation affects the business cycle, quantify its impact on long-term economic growth, and evaluate policy strategies for managing inflation’s adverse effects. Methodologically, we employ panel data analysis using econometric models across a sample of countries from 1990 to 2021. This approach allows for cross-country compari-sons and controls for country-specific factors, providing robust estimates of inflation’s impact on GDP growth, unemployment, and investment. The findings indicate a statistically significant negative relationship between high inflation and GDP growth, especially when inflation rates exceed 10%. Additionally, inflation is shown to reduce investment levels and increase unemployment, aligning with Phillips curve implications in the short term and supporting inflation neutrality in the long run as expectations adjust. Theoretically, this study contributes to existing literature by confirming the threshold effect of inflation on growth, where moderate inflation may coexist with growth but high inflation disrupts economic stability. Methodologically, the use of panel regression models highlights the efficacy of country-level fixed effects in capturing infla-tion’s diverse impacts across different economic contexts. Practically, the research underscores the importance of inflation-targeting frameworks, counter-cyclical fiscal policies, and structural reforms to enhance resilience and support sustained economic growth. These insights offer val-uable guidance for policymakers seeking to balance inflation control with economic stability.